2013
DOI: 10.1111/add.12400
|View full text |Cite
|
Sign up to set email alerts
|

Reduced fetal growth in methadone-maintained pregnancies is not fully explained by smoking or socio-economic deprivation

Abstract: Reduced fetal growth in infants of opioid-dependent mothers prescribed methadone maintenance in pregnancy is not fully explained by cigarette smoking, area deprivation, maternal age or parity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 26 publications
(45 reference statements)
2
25
0
Order By: Relevance
“…Methadone in pregnancy is associated with improved antenatal care, reduced maternal morbidity and improved neonatal outcomes (Burns et al, 2007) although a recent study found low birth weight in those on treatment compared to general population (Mactier et al, 2014). There are less data regarding buprenorphine in pregnancy, though evidence is increasing Minozzi et al, 2013b;Wurst et al, 2016).…”
Section: Opioid Misuse/dependencementioning
confidence: 99%
“…Methadone in pregnancy is associated with improved antenatal care, reduced maternal morbidity and improved neonatal outcomes (Burns et al, 2007) although a recent study found low birth weight in those on treatment compared to general population (Mactier et al, 2014). There are less data regarding buprenorphine in pregnancy, though evidence is increasing Minozzi et al, 2013b;Wurst et al, 2016).…”
Section: Opioid Misuse/dependencementioning
confidence: 99%
“…Consequently, it is possible that prenatal opioid contact has an adverse neurological outcome on humanoid fetuses. Children born to mothers involved in opioid and poly-substance consumption during pregnancy regularly have less birth weight than control groups (43,44). Low birth weight has been proven to be a prognosticator of later cognitive capacities (45,46), socio-emotional functioning, decision-making functioning, academic success and neuroanatomical physiognomies, even for normal birth weight variants (32).…”
Section: Pathophysiology and Etiologymentioning
confidence: 99%
“…[43][44][45][46] Long-term effects on cognition and behavior: Heavy maternal alcohol consumption during pregnancy is associated with neuropsychological difficulties in affected children ranging from subtle learning and/or behavioral problems to severe intellectual impairment. 12,47 A variety of behavioral and cognitive difficulties, including deficits in visuospatial functioning, memory and learning, attention, selfregulation, executive functioning and motor skills are commonly seen. 47 There is convincing evidence that detrimental effects of alcohol on the developing fetal brain underlay these neurobehavioral problems, with proposed mechanisms of neurotoxicity supported by extensive animal-and cell culture research.…”
Section: -21mentioning
confidence: 99%
“…12,47 A variety of behavioral and cognitive difficulties, including deficits in visuospatial functioning, memory and learning, attention, selfregulation, executive functioning and motor skills are commonly seen. 47 There is convincing evidence that detrimental effects of alcohol on the developing fetal brain underlay these neurobehavioral problems, with proposed mechanisms of neurotoxicity supported by extensive animal-and cell culture research. [48][49][50] A wide range of neuropsychological impairments have also been associated with prenatal exposure to drugs other than alcohol, however, a far more limited number of studies exist to answer whether these impairments are caused by specific drugs.…”
Section: -21mentioning
confidence: 99%
See 1 more Smart Citation